The lost art of Heinrich Kley - Kley, Heinrich, 1863-1945; Kunkel, Alexander; Kaluta, Michael William; Hamm, Jesse; Procopio, Joseph Vincent, 1970- (Silver Spring, Md. : Picture This Press, 2012)
he Lost Art of Heinrich Kley Volumes One and Two collect over 450 drawings and paintings from a wide array of sources. Neither volume overlaps with past books on Kley, as nearly none of these drawings have been collected and reprinted since their original publication a century or more ago. Both volumes also provide groundbreaking scholarship on Kley's life and work by German art historian Alexander Kunkel - whose recent research is presented in these volumes for the first time in English - along with incisive appreciations by contemporary artists Michael Wm. Kaluta and Jesse Hamm. --Publisher's description
Volume. 1. Drawings Volume 2. Paintings and sketches.
Appreciation: Kley's distinction/ Jesse Hamm--v. 2.
Keywords: Kley, Heinrich, -- 1863-1945; Illustrators -- Germany